Unveiling the synergistic effect of icariin and azole drugs on Candida albicans - Aliaghazadeh, Barbod; Pascual-Ortiz, Marina; Martínez, Alba; Veses, Veronica; Sheth, Chirag C. (Frontiers in Oral Health, 2025)
Introduction and MethodThe current study explores the synergistic effects of icariin, a flavonoid found in plants of the genus Epimedium, in ombination with selected antifungal agents, against Candida albicans in vitro.ResultsThis flavonoid significantly enhanced the in vitro effect of fluconazole, by decreasing the minimum inhibitory concentration against C. albicans. This effect was also observed when combining icariin with ketoconazole and itraconazole of the azole family respectively. Interestingly, no activity-enhancing effect was observed when icariin was combined with other classes of antifungals, such as amphotericin B or caspofungin.DiscussionWe conclude that icariin may increase the sensitivity of C. albicans to azoles via a cell membrane mediated mechanism, based on our results from FUN-1 microscopy and coincubation with cell wall and cell membrane stressors. Further research is required to explore these effects in clinical isolates, particularly fluconazole-resistant C. albicans, with a view towards the clinical application of icariin as a co-adjuvant in antifungal azole therapy.